XIMIYA SABAQLIǴIN OQITIWDA INFORMACIYALIQ TEXNOLOGIYALARINAN PAYDALANIW - Jumamuratov, R.E.; Kaipbergenov, A.T.; Aynazarova, S.S. (SCIENCE and SOCIETY, 2022)
The article is devoted to the use of computer technologies in chemical education. Computer is a source of information, training, evaluation, control, teacher - the choice of teaching material, organization of individual work in the classroom, management of the process of independent learning activities of students, organization of objective forms of control.